2015
DOI: 10.1136/vetreco-2015-000123
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Neospora caninum seroprevalence and potential impact on reproductive success in semi‐free‐ranging Père David's deer (Elaphurus davidianus)

Abstract: This study aimed to determine the prevalence and reproductive impact of Neospora caninum in a herd of semi-free-ranging Père David's deer (Elaphurus davidianus) at a conservation facility, following a suspected abortion storm in 2008. Serum samples (n=103) collected from 60 individuals between 2002 and 2011 were evaluated using competitive ELISA for the detection of N. caninum-specific antibodies. Of the 103 samples, 73 (70.9 per cent) were positive for N. caninum antibodies, with a mean±sd competitive inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…We were unable to test associations for Père David’s deer; however, a previous retrospective study on N . caninum seroprevalence in the Père David’s deer herd found no correlation between calving rates and seropositivity [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We were unable to test associations for Père David’s deer; however, a previous retrospective study on N . caninum seroprevalence in the Père David’s deer herd found no correlation between calving rates and seropositivity [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, seroprevalence studies in cattle, buffalo and Père David’s’ deer have suggested both age-specific and constant N . caninum prevalence with age [ 43 , 45 48 ]. In our study none of the three ruminant populations showed age-structured FoI.…”
Section: Discussionmentioning
confidence: 99%